2010
DOI: 10.1097/cji.0b013e3181dda23e
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccine Encoding Prostatic Acid Phosphatase (PAP) Elicits Long-term T-cell Responses in Patients With Recurrent Prostate Cancer

Abstract: SummaryProstatic acid phosphatase (PAP) is a tumor antigen in prostate cancer and the target of several anti-tumor vaccines in earlier clinical trials. Ultimately, the goal of anti-tumor vaccines is to elicit a sustainable immune response, able to eradicate a tumor, or at least restrain its growth. We have investigated plasmid DNA vaccines and have previously conducted a phase 1 trial in which patients with recurrent prostate cancer were vaccinated with a DNA vaccine encoding PAP. In this study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 23 publications
3
90
0
1
Order By: Relevance
“…An alternative immunotherapeutic approach for prostate cancer-associated antigens uses cell-free DNA plasmids (24,25). Despite their relative ease of GMP production and less complex regulatory issues, so far these vaccines have been unable to induce a high frequency of NCI RECIST criteria clinical responses or strong immune responses in the clinic.…”
Section: Anti-prostate Cancer Dna Vaccinesmentioning
confidence: 99%
“…An alternative immunotherapeutic approach for prostate cancer-associated antigens uses cell-free DNA plasmids (24,25). Despite their relative ease of GMP production and less complex regulatory issues, so far these vaccines have been unable to induce a high frequency of NCI RECIST criteria clinical responses or strong immune responses in the clinic.…”
Section: Anti-prostate Cancer Dna Vaccinesmentioning
confidence: 99%
“…In contrast to TRAMP mice, the castration in TRAP rats at 5 or 20 wk of age completely prevented or induced a complete involution of androgen-dependent prostate tumors in the most of transgenic rats [45,46] . Of therapeutic interest, since the prostate-specific antigen and prostate acid phosphatase (PAP) are expressed in rat prostate as observed in human prostate but not in mouse prostate, TRAP rats may constitute a good animal model to test novel vaccine strategies targeting these antigens [46,52] . For instance, it has been observed that the immunization of Lewis TRAP rats with a DNA vaccine encoding PAP triggered an autologous PAP-specific T-cell responses in transgenic rats [46] .…”
Section: Inflammation and Pcmentioning
confidence: 99%
“…No significant adverse events were detected, and ten of 22 patients generated PAP-specific T-cell responses immediately after immunization [57]. Responses observed were Th1 type, and cytolytic T-cell responses were specifically elicited in HLA-A2-expressing subjects [58]. Approximately 1/3 of individuals were observed to have at least a 100% increase in PSA doubling time, and this was associated with the detection of long-term PAP-specific IFNγ-secreting immune responses detectable at multiple times during the follow up period (up to 1 year after immunization).…”
Section: Introduction: Cancer Immunotherapy and Anti-tumor Vaccinesmentioning
confidence: 99%
“…Approximately 1/3 of individuals were observed to have at least a 100% increase in PSA doubling time, and this was associated with the detection of long-term PAP-specific IFNγ-secreting immune responses detectable at multiple times during the follow up period (up to 1 year after immunization). PAP-specific CD8+ T-cell immune responses were detected at each dose level, and one patient treated at the lowest (100 μg) dose was subsequently re-immunized at this dose with evidence of immune response, making the 100 μg dose the dose chosen for further trials [58]. Given the safety, immunological efficacy, and prolongation of PSA doubling time observed in some individuals, a randomized phase II clinical trial is currently underway to evaluate the 2-year metastasis-free rate in high-risk individuals (PSA doubling time less than 12 months) in patients treated with this vaccine or GM-CSF adjuvant alone (NCT01341652).…”
Section: Introduction: Cancer Immunotherapy and Anti-tumor Vaccinesmentioning
confidence: 99%